Handbook on health inequality monitoring : with a special focus on low- and middle-income countries (Nonserial Publications., 2013)
"The Handbook on health inequality monitoring: with a special focus on low- and middle-income countries is a resource that enables countries to do just that. It presents a comprehensive yet clear overview of health inequality monitoring in a user-friendly manner. The handbook succeeds in giving those involved in health inequality monitoring an appreciation of the complexities of the process, as well as building the practical knowledge and skills for systematic monitoring of health inequalities in low- and middle-income countries. The use of the handbook will enable countries to better monitor and evaluate their progress and performance with a high degree of accountability and transparency, and allow them to use the results to formulate evidenced-based policies, programmes and practices to tackle inequalities in an effective manner."--Publisher's description